In vitro study on α-amylase and α-glucosidase inhibitory activities of a new stigmastane-type steroid saponin from the leaves of Vernonia amygdalina. Issue 5 (4th March 2021) - Anh, Hoang Le Tuan; Vinh, Le Ba; Lien, Le Thi; Cuong, Pham Viet; Arai, Masayoshi; Ha, Tran Phuong; Lin, Hoang Ngoc; Dat, Ton That Huu; Cuong, Le Canh Viet; Kim, Young Ho
Abstract: Using various chromatographic separations, four compounds, including one new steroid saponin named vernoamyoside E (1 ), were isolated from the leaves of the Vietnamese medicinal plant Vernonia amygdalina Delile (Asteraceae). Their structures were established by spectroscopic methods such as 1D- and 2D-NMR, HR-ESI-MS, and HPLC analysis. The inhibitory activities against α-glucosidase and α-amylase of the isolated compounds from V. amygdalina were reported for the first time. The results indicated that compound 1 significantly inhibited both against α-amylase and α-glucosidase activity. Graphical Abstract: